In vitro anticancer and antifungal effects of Lactobacillus paracasei supernatants: a step toward sustainable food systems - Erdal, Berna; Yilmaz, Bahar; Bozgeyik, Esra; Yıkmış, Seydi; Mohamed Ahmed, Isam A.; Aljobair, Moneera O.; Trif, Monica (Frontiers in Sustainable Food Systems, 2025)
Sustainability in food systems increasingly involves the integration of natural bioactive compounds that support human health while promoting eco-friendly production processes. Probiotic microorganisms, particularly those derived from food systems, have gained growing attention due to their dual role in health promotion and sustainable biotechnological applications. This study investigates both the anticancer and antifungal properties of live and thermally inactivated cell-free supernatants (CFSs) of Lactobacillus paracasei subsp. paracasei, a food-grade probiotic, thereby addressing a significant research gap in the dual-functional potential of probiotic metabolites. Human glioma (U-87) and non-cancerous kidney epithelial (HEK293T) cells were treated with live and inactivated CFSs. A dose-dependent cytotoxic effect was observed, with IC₅₀ values indicating greater selective efficacy of the inactivated CFSs against glioma cells, while sparing normal cells. Flow cytometry and fluorescence microscopy revealed that both CFSs induced apoptosis and cell cycle arrest at the sub-G1 phase, findings further supported by DNA fragmentation analysis. In parallel, antifungal activity against Candida albicans and Candida parapsilosis was evaluated using the broth microdilution method. Notably, the inactivated CFSs exhibited potent fungistatic and fungicidal effects at lower concentrations than the live form, highlighting a novel, stable postbiotic alternative with therapeutic relevance. The present study is the first study to simultaneously demonstrate selective anticancer activity against U-87 glioma cells and broad-spectrum antifungal potential of inactivated L. paracasei CFSs. These findings represent a promising strategy for integrating probiotic-derived bioactives into sustainable food systems and functional food development.